2011
DOI: 10.1080/00405000.2011.564797
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency and its determinants in the Indian garment industry

Abstract: One of the recommendations of the Textile Expert Committee, India, was to set a Technology Demonstration Centre to address the issues related to improvement in productivity and efficiency of the Indian garment industry. The committee identified the key factors responsible for the low level of production efficiency, which were low labour and capital productivities, high capital cost, outdated technology and low-skilled workers. In the light of subsequent recommendations made by the committee, the researchers ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 16 publications
0
20
1
1
Order By: Relevance
“…The extent and intensity of the factors use, namely, fuel, capital and labor, and decide the success of the industry. Nevertheless, the policy restrictions have affected the firms' investment and machinery that prevented firms from achieving economies of scale (Joshi and Singh, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent and intensity of the factors use, namely, fuel, capital and labor, and decide the success of the industry. Nevertheless, the policy restrictions have affected the firms' investment and machinery that prevented firms from achieving economies of scale (Joshi and Singh, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Joshi and Singh's study (2012) provided a complete overview of the manufacturing sector and trends since independence. In the Indian context, only a few studies have been carried out on the textile industry's technical efficiency-related issues (Bhandari and Ray, 2012;Bhaskaran, 2013;De Jorge-Moreno and Carrasco, 2015;Joshi and Singh, 2012). Recent developments in the Industry 4.0 revolution have created constructive disruption (Schumpeter, 1954) and shaken the foundation of the manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the methodological domain of EC has evaluated trends by mostly considering empirical studies only. A number of attempts have been made by previous researchers to understand the methodologies adopted; for instance, two stage least square method (Frankel and Romer, 1999; Morgan, 2013), constant market share model (Joshi and Singh, 2012), simple general equilibrium model of EC (Helpman, 1984), RCA (Qureshi and Wan, 2008), MNL model (Rettab and Rao, 2009), gravity model (Bergstrand, 1985; Fink et al , 2005), tobit model (Kumar and Siddharthan, 1994), auto regressive conditional heteroscedasticity model (McKenzie and Brooks, 1997), GARCH model (Kroner and Lastrapes, 1993), probit, logit and tobit and MNL logistic (Hung et al , 2004). We make a strong point here that authors should compile more studies to put forward a more comprehensive integration of all the relevant facets of the methodological domain.…”
Section: Directions For Future Research (Future Research Agenda)mentioning
confidence: 99%
“…NIC 1998 and 2004 for sugar mills is 15,421 and 10,721 for NIC 2008. After reviewing the literature, it was found that Abdulla (2017), Bhandari and Vipin (2016), Mukherjee (2008), Mukherjee and Ray (2004) and Joshi and Singh (2012) also used ex-factory value of output as an output variable and fixed capital, fuels consumed, wages salary and raw material consumed as input variables to assess the efficiency of manufacturing sector in India. The variables used in the study deflated by using appropriate deflator.…”
Section: Data Sourcementioning
confidence: 99%